Natural Resources, Volatility, and Inclusive Growth : Perspectives From the Middle East and North Africa - Nabli, Mustapha; Arezki, Rabah (Washington, D.C. : International Monetary Fund, 2012)
This paper takes stock of the economic performance of resource rich countries in the Middle East and North Africa (MENA) over the past forty years. While those countries have maintained high levels of income per capita, they have performed poorly when going beyond the assessment based on standard income level measures. Resource rich countries in MENA have experienced relatively low and non inclusive economic growth as well as high levels of macroeconomic volatility. Important improvements in health and education have taken place but the quality of the provision of public goods and services remains an important source of concerns. Looking forward we argue that the success of economic reforms in MENA rests on the ability of those countries to invest boldly in building inclusive institutions as well as high levels of human capacity in public administrations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet